Secret Channel using Video Steganography - Lee Kar Yee; Chuah Chai Wen (JOIV : International Journal on Informatics Visualization, 2017)
Video steganography is about hiding the secret message into the video as the cover media. Steganography is a technique use to secure the transmission of secret information or hide their existence. Most of the steganography software such as DeEgger Embedder and OurSecret does not have encryption algorithm to preserve the confidentiality for the secret message. OurSecret software only using simple password to keep the secrecy of the message. A simple password is not strong enough to protect the secret message, secret message will be vulnerable once the attacker successfully attack the steganography technique use to hide the secret message in the video. Furthermore, password is not an encryption algorithm. Secret message without encrypted is the vulnerability to the secret message. Confidentiality of the secret message will not be able to preserve. Hence there is a need to encrypt the secret message with stream cipher while not leaving it vulnerable to attacker. Stream cipher provide bit by bit encryption. A video steganography with embedding text with RC4 encryption cipher is design, develop and test in this project.